2011
DOI: 10.1016/j.neucom.2011.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Online learning neural tracker

Abstract: Object tracking is a fundamental computer vision problem and is required for many high-level tasks such as activity recognition, behavior analysis and surveillance. The main challenge in the object tracking problem is the dynamic change in object/background appearance, illumination, shape and occlusion. We present an online learning neural tracker (OLNT) to differentiate the object from the background and also adapt to changes in object/background dynamics. In the proposed tracking system, we propose a new mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This method uses information from the first frame to train the NN with no further model updating. Suresh et al presented an online learning neural tracker with radial basis function network, and the learning algorithm updates the parameters of the nearest neuron to reduce the computational complexity [30]. Serratosa et al exploited a probabilistic integrated object recognition and tracking framework with respectively Bayesian method and a multilayer perceptron, and their test results showed that the perceptron method outperforms the Bayesian [31].…”
Section: Introductionmentioning
confidence: 99%
“…This method uses information from the first frame to train the NN with no further model updating. Suresh et al presented an online learning neural tracker with radial basis function network, and the learning algorithm updates the parameters of the nearest neuron to reduce the computational complexity [30]. Serratosa et al exploited a probabilistic integrated object recognition and tracking framework with respectively Bayesian method and a multilayer perceptron, and their test results showed that the perceptron method outperforms the Bayesian [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, neural networks are applied in various domains such as classification problems [1]- [9] and for prediction [10] [11], Control system [12]- [14], workstations [15], aeronautical engineering [16] and human-machine interface [17]. Recently, multidisciplinary Brain Computer Interface researches are taking place in a rapid pace for providing communication abilities for people with rigorous motor disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The domain of artificial neural network are applied for classification problems [1] and for prediction, Control systems [2][3]etc.,. Recently, the data in the applications like signal processing [4], [5], image processing [6] and communication [7], etc., are naturally complex-valued in nature and varies with time.…”
Section: Introductionmentioning
confidence: 99%